POLITIK KAUM SANTRI DALAM SEJARAH INDONESIA - Ja’far, Suhermanto (Jurnal Review Politik, 2012)
This article  is a historical analysis about the politics of  santri. The role and involvement of santri in politics is not a new phenomenon, although the quality and quantity in each political episode is different, but the process and dynamics of Indonesian politics, can not be separated from the involvement of santri. This position is in line with the actual political map of Indonesia. The involvement of santri can describe in four times of the history of Indonesia, namely the pre-independence era, the early of independence until the end of the old order, the new order, and reform era. The fourth periodicity are used to read and analyze the tides of gait of santri in the political world.